A Comparison of the South African and United States Models of Natural Areas Management. (28th January 2014) - Licht, Daniel S.; Kenner, Brian C.; Roddy, Daniel E.
Abstract : In May-June of 2013 we visited several South African parks and reserves to learn about wildlife and natural areas management in that country. We focused our visit on parks and reserves that are of moderate size (5, 000–100, 00 ha), comprised of grassland/savanna habitats, located within agrarian landscapes, and enclosed with boundary fences, characteristics similar to several parks and reserves in the Northern Great Plains region of the United States. In this paper we compare the South African model of natural areas management to the United States model. We observed that South African parks and reserves with the aforementioned characteristics are more likely to (1) reintroduce and conserve small, nonviable wildlife populations, (2) reintroduce and conserve top-level predators, (3) have more intensive management of wildlife, (4) manage in partnership across multiple landowners, (5) engage local communities, (6) be self-funding, and (7) restrict visitor movement. The South African model is arguably more effective in conserving biodiversity as measured by conservation of apex predators and natural processes. The differences between the countries appear to be driven in large part by socioeconomic factors. Knowledge of natural areas management in other countries may lead to more innovative and creative models that could benefit biodiversity conservation.